(untitled) (Journal of the College of Basic Education, 2022)
The contemporary theatrical movement produced different external and technical methods that were adopted to create New aesthetic spaces according to the values ​​of plastic art and the elements of architectural construction. The sino-arvia is the visual diligence presented by the theatrical show, which is established through Employment of the initial ritual according to the propositions of (Antonin Artaud), in which he relied on the transformation of the offer theatrical into an aesthetic ritual in which both the actor and the recipient unite within a visual space that is Alsinork Arvia and rituals most prominent features. The creation of the sino-arvi of the theatrical space was a privilege For theatrical experimentation, hence the research problem (discovering the ambiguity of the concept of synographia